Pengungkapan Pro Forma, Mendukung atau Menyesatkan Investor? - Rura, Yohanis (Jurnal Akuntansi Multiparadigma, 2010)
Pro forma is originated from Latin. It contains different meaning depends on which discipline it is used. In accounting, pro forma disclosure is used to show effect of important transaction which occurs after the end of periods, or which occurs during period but not fully reflected in historical cost financial statement of a firm. Pro forma disclosure has the objective to support (but might mislead) investor in decision making focused on particular influence of important transaction. Company with low GAAP profit information; less profitable company and has higher level of debt but more liquid, whose P-E ratio and market to book is higher than other companies in the industry; has the tendency to do pro forma disclosure. Pro forma disclosure has been supported by several theories such as: efficient market theory, catering theory, agency theory, signaling theory, and stakeholder theory. However, there are problems in reporting pro forma figures. There is no standard to it. Therefore, information on pro forma disclosure might also mislead less sophisticated investor.